Identifying Place Distinctiveness Through Cultural Resource Mapping - Nur Farhana Azmi; Faizah Ahmad; Azlan Shah Ali (Journal of Regional and City Planning, 2021)
Regardless of their size, every town, city, or more generally each place, has its own beautiful, unique and distinct characteristics. However, only few studies have provided valuable information on exceptional and unique features that can contribute to the distinctiveness and identity of small-scale towns. It is important to identify these cultural resources, especially now that the identity of small towns is rapidly weakening. This study explored the significance of cultural resource mapping as an important technique for identifying the unique characteristics of a place. A questionnaire survey was conducted amongst a random sample of 119 local community members in Sungai Lembing, a small town in the state of Pahang, Malaysia, to investigate respondents’ mental representations of familiar features that they experience in the town, through cultural mapping. It was revealed that natural features, buildings, and non-building structures were seen by the respondents as the most dominant elements that constitute the individuality of their town. While deepening the community’s understanding and awareness of their cultural assets, this paper also highlights the significance of cultural mapping as a tool for identifying unique characteristics of a place, especially those that may have been previously overlooked.   Abstrak. Terlepas dari ukurannya, setiap kota atau lebih umum lagi suatu tempat, memiliki keindahan, keunikan dan karakter tersendiri. Namun, hanya sedikit penelitian yang memberikan informasi berharga tentang fitur luar biasa dan unik yang dapat berkontribusi pada kekhasan dan identitas kota skala kecil. Oleh karena itu, penting untuk mengidentifikasi sumber daya budaya tersebut terutama dalam kondisi saat ini di mana identitas kota kecil dengan cepat melemah. Makalah ini mencoba mengeksplorasi pentingnya pemetaan sumber daya budaya sebagai teknik penting untuk mengidentifikasi karakteristik unik suatu tempat. Survei kuesioner dilakukan di antara sampel acak dari 119 komunitas lokal di Sungai Lembing, sebuah kota kecil di negara bagian Pahang, Malaysia; untuk menyelidiki representasi mental responden dari fitur-fitur yang sudah dikenal yang dialami di kota melalui pemetaan budaya. Studi ini mengungkapkan bahwa fitur alam, bangunan dan struktur non-bangunan digambar oleh responden sebagai elemen dominan yang membentuk individualitas kota. Sambil memperdalam pemahaman dan kesadaran masyarakat akan aset budaya mereka, makalah ini juga menyoroti pentingnya pemetaan budaya sebagai salah satu alat penting dalam mengidentifikasi karakteristik unik suatu tempat terutama yang mungkin sebelumnya diabaikan.   Kata kunci. pemetaan budaya, dokumentasi, identitas, tempat, kota kecil.